Technical efficiency and productivity potential of cocoa farmers in West African countries - Binam, Joachim N.; Gockowski, J.; Nkamleu, G.B. (Wiley, 2008)
This paper uses survey data to examine the technical efficiency and productivity potential of cocoa farmers in West and Central Africa. Separate stochastic frontier models are estimated for farmers in Cameroon, Ghana, Nigeria, and Côte d’Ivoire, along with a stochastic metaproduction frontier to obtain alternative estimates for the technical efficiencies of farmers in the different countries. The mean productivity potential of cocoa farmers is also estimated, by using a decomposition result applied to both the national and the metaproduction frontiers. The determinants of technical efficiency are assessed to identify the reasons for differences across countries.